Morphology of a unique ophidiid, Hypopleuron caninum Radcliffe 1913 (Ophidiiformes, Ophidiidae, Neobythitinae), suggesting a close relationship with the family Carapidae - Ohashi, Shinpei (Zootaxa, 2018)
Osteological and myological characters of the ophidiid Hypopleuron caninum are described here in detail. In addition to well-known characters of Ophidiidae (e.g., anal-fin origin well posterior to dorsal-fin origin; barbel-like pelvic fin; many scales), many unique or rare conditions were also recognized, including predorsal bone and maxilla condition, and canine teeth on the premaxilla, which were suggestive of a relationship with Carapidae. Furthermore, the predorsal bone appear to be homologous with the vexillar support, a carapid synapomorphy. Although several characters differ from carapid counterparts (e.g., more anterior anal-fin origin and scales absent in Carapidae), some intermediate conditions between Ophidiidae and Carapidae are apparent in Hypopleuron caninum, which may therefore occupy an intermediate phylogenetic position between the two families. A unique morphology of small second infraorbital bone is recognized in all ophidiiform species observed in this study, and it may be a synapomorphic character of the order Ophidiiformes.